PECULIARITIES OF THE IMMUNE STATUS AND CLINICAL FEATURES OF IMMUNODEFICIENCY IN PATIENTS WITH VENTRAL HERNIA - E. N. Kologrivova (SPb RAACI, 2014)
Abstract. Clinical and immunological investigation of 103 patients with postoperative ventral hernia including the detection of lymphocytes subpopulations, the levels of IL–4, IFNγ and clinical manifestation of immune deficiency was carried out. The patients with postoperative ventral hernia had various changes of cells immunity connected with obesity. The low level of cytokines in all patients and disbalans of Th1– and Th2–cells have beenrevealed. The analyses of revealed abnormalities in comparison the results of clinical investigations were carried out. The results of this work are recommended to take into account during preoperative and postoperative periods. (Med. Immunol., 2005, vol.7, № 5–6, pp. 563–568)